2019
DOI: 10.3389/fncel.2019.00339
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Prion Protein as a Receptor of Toxic Amyloid-β42 Oligomers Is Important for Alzheimer’s Disease

Abstract: The pathological features of Alzheimer’s disease (AD) include senile plaques induced by amyloid-β (Aβ) protein deposits, neurofibrillary tangles formed by aggregates of hyperphosphorylated tau proteins and neuronal cell loss in specific position within the brain. Recent observations have suggested the possibility of an association between AD and cellular prion protein (PrP C ) levels. PrP C is a high affinity receptor for oligomeric Aβ and is important for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 67 publications
1
56
0
Order By: Relevance
“…The significance of PrP C in the pathogenesis of AD stems from its role as a receptor for Aβ oligomers [ 142 , 143 ]. Aβ 1−42 specifically binds PrP C with high affinity in a saturable and reversible manner, and mediates biologically relevant downstream intracellular signaling events including the loss of synaptic function, impaired memory and cognition, and other functional deficits associated with AD [ 144 , 145 ]. Two binding sites of Aβ have been identified on PrP C : residues 95−105 and residues 23−27 [ 143 ] ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The significance of PrP C in the pathogenesis of AD stems from its role as a receptor for Aβ oligomers [ 142 , 143 ]. Aβ 1−42 specifically binds PrP C with high affinity in a saturable and reversible manner, and mediates biologically relevant downstream intracellular signaling events including the loss of synaptic function, impaired memory and cognition, and other functional deficits associated with AD [ 144 , 145 ]. Two binding sites of Aβ have been identified on PrP C : residues 95−105 and residues 23−27 [ 143 ] ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The best known example is the PrPc-AβO interaction and the subsequent signalization cascade [115][116][117]. The simplified pathway is the following (Figure 4): AβO binds to PrPc, then stimulates the Proto-oncogene tyrosine-protein kinase Fyn by activating the metabotropic GluR5.…”
mentioning
confidence: 99%
“…Previous studies have suggested that the cell surface protein PrP C mediates the toxicity of Aβ 42 oligomers by binding to them and affecting synaptic plasticity and other neuronal functions [ 13 , 14 , 15 , 16 , 17 , 18 ], although a general consensus on this point has not yet been found [ 19 , 20 , 21 ]. One PrP C region of the sequence thought to be involved in Aβ 42 binding encompasses approximately residues 95–110 [ 13 , 14 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 ]. An antibody raised against residues 93–109 of PrP C (anti-PrP C 93–109 GD11) and a synthetic peptide corresponding to residues 98–107 (PrP 98–107 ) were found to inhibit the toxicity of the Aβ 42 ADDLs to organotypic hippocampal slices, whereas a control PrP 213–230 peptide did not have any such effects [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of data have shown that PrP C has a high binding affinity for Aβ 42 oligomers [ 33 , 34 ]. Even studies showing that PrP C -expressing and PrP C knock-out mice were equally susceptible to Aβ 42 oligomer-induced cognitive impairment recognized that the oligomers interacted with PrP C with high affinity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation